Agritourism Management Visitors Expectation and Destination Performance - Wiranatha, Agung Suryawan; Petr, Christine; Suryawardani, I Gusti Ayu Oka; Purbanto, I Gusti Raka; Yudiastina, I Gusti Bagus Arya (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 18 No 1 (2024): Vol 18 No 1 (2024), 2024)
Agritourism has become a travel trend for the travelers who enjoy visiting villages which are supported by the concept of back to nature. Understanding behavior of visitors in enjoying open space destination will be useful for the future visitation plan of traveler who prefer visiting nature, environment, and the beauty of landscape in the rural area.  The research aimed: (i) to find out visitors’ hope based on performance of Jatiluwih agritourism, and (ii) to formulate strategy to develop Jatiluwih Agritourism.  Location of this research was Jatiluwih agritourism which was chosen because the number of visitors has been low compared to other nature-based destinations, such as Melasti and Pandawa beaches. Data was collected on January to April 2022 through distributing questionnaires to 300 visitors. Likert Scale was used to analyze the data in 1 – 5 scale. The number of indicator was nine. Visitors’ satisfaction of Jatiluwih agritourism was assessed by using important and performance approach. The results show that (i) Level of destination performance of Jatiluwih Agritourism to all indicators was lower than visitors’ expectation.  Level of visitors’ expectation for each indicator are as follow: a) level of visitors’ expectation on attraction, healthy and comfortability were higher than the destination performance, and b) level of expectation of visitors on accessibility and amenity were lower than the destination’performance. Strategy to develop Jatiluwih Agritourism i.e., to improve the quality of cleanliness and health aspects as the main priority; to develop a better accessibility; to maintain the attractions; to maintain the hospitality, safety and comfortability of visitors